Immortalized endothelial cell lines for in vitro blood-brain barrier models: a systematic review - Rahman, Nurul Adhwa; Meyding-Lamadé, Uta (Brain research, 2016)
Endothelial cells play the most important role in construction of the blood-brain barrier. Many studies have opted to use commercially available, easily transfected or immortalized endothelial cell lines as in vitro blood-brain barrier models. Numerous endothelial cell lines are available, but we do not currently have strong evidence for which cell lines are optimal for establishment of such models. This review aimed to investigate the application of immortalized endothelial cell lines as in vitro blood-brain barrier models. The databases used for this review were PubMed, OVID MEDLINE, ProQuest, ScienceDirect, and SpringerLink. A narrative systematic review was conducted and identified 155 studies. As a result, 36 immortalized endothelial cell lines of human, mouse, rat, porcine and bovine origins were found for the establishment of in vitro blood-brain barrier and brain endothelium models. This review provides a summary of immortalized endothelial cell lines as a guideline for future studies and improvements in the establishment of in vitro blood-brain barrier models. It is important to establish a good and reproducible model that has the potential for multiple applications, in particular a model of such a complex compartment such as the blood-brain barrier.
Gesehen am 27.01.2021